The pros and cons artificial intelligence (AI) brings to the working industry / Inda Rasyidah Nazrul Azha - Nazrul Azha, Inda Rasyidah (Jabatan Perpustakaan Digital (JPDg), 2024)
Now, what is Artificial Intelligence? it is described as technology that enables computers and machines to simulate human like intelligence and including problem solving capabilities, I'm pretty sure all of you guys have experienced and played around with AI like Chat GPT, AI image generators even using those text summarizers or paraphrases and but before this there's also things like that you’ve use like Google Maps or even Siri on your iPhone there's also face recognition, image recognition and so forth.